Environmental responsibility and communication in selected companies in the Podravska statistical region - Virant, Zala (Acta geographica Slovenica, 2024)
The paper presents best practices pursued by eight companies from the Podravska statistical region selected because they promote green transition in this society. In the theoretical section, the article presents environmental responsibility as part of corporate social responsibility and deals with the type of communication needed to address and motivate people to implement the EU Green Deal goals. The empirical section analyses eight semi-structured interviews with representatives from selected companies in the Podravska statistical region. The results highlight long-term efforts to raise public awareness about the environmental crisis (without major visible effects), financial aid as the main motivation factor to implement green practices, shortage of specific training courses in communication, and the need for locally focused training.
Keywords: communication; ekologija; environmental responsibility; green motives; Okoljska odgovornost; Okoljska politika; Podjetja; Podravje; Podravska statistical region; poslovno komuniciranje; sustainability; sustainable organisational practices; trajnostni razvoj; varstvo okolja